Thawing Time Difference between Fresh Frozen Plasma Using Ziplock Plastic and non-Ziplock Plastic in Blood Transfusion Unit Dr. Hasan Sadikin General Hospital Bandung, Indonesia - Rinanty, Rima; Lismayanti, Leni; Harahap, Raja Iqbal Mulya (Faculty of Medicine Universitas Padjadjaran, 2023)
Background: The quality of fresh frozen plasma (FFP) in a clinical setting depends on thawing time. Thawing using a water bath is often used in blood transfusion units because it is easy to perform, affordable, and easy to look for. Protective plastics (Ziplock and non-Ziplock) are used to reduce the risk of contamination,. This study aimed to determine whether there is a difference in thawing time between FFP using Ziplock plastic and non-Ziplock plastic.Method: This experimental design was conducted in the Blood Bank Unit of Hasan Sadikin Hospital from June-August 2021. Samples were divided into two groups, namely thawing using Ziplock and non-Ziplock. Each group consisted of volume 160-200 ml and 201-240 ml.Results: The total samples were 24 FFP bags. In the group of the bag 160-200 ml, the median thawing time using Ziplock plastic was 8 minutes (8-16 minutes), non-Ziplock was 15 minutes (8-16 minutes) (p value 0,111), whereas in a group of bags with volume 201-240 ml, the median thawing time using Ziplock was 15 minutes (8-28 minutes), non-Ziplock was 20 minutes (14-30 minutes) (p- value 0,332). Although there was a time difference in both groups, the difference was non-significant.Conclusion: The thawing time between the small bag with a volume of 160-200 ml and the larger volume of 201-240 ml shows no difference. Ziplock plastic can be used to reduce the risk of contamination.